Abrupt Changes in Weather in Uzbekistan: Causes, Consequences and Ecological Solutions - Suyunova Xulkar To‘lqin qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article analyzes the sharp changes in weather conditions observed in Uzbekistan, the global and local factors influencing their formation, and the economic, ecological and social consequences of this process. The process of climate change, which is intensifying globally, is having a significant impact on the Central Asian region, in particular Uzbekistan. Such phenomena as increased air temperature, reduced precipitation, water shortages, and increased dust storms are becoming increasingly relevant issues today. The article also proposes practical solutions aimed at increasing the ecological culture of the population, protecting nature, and strengthening advocacy work to ensure ecological sustainability.